Perlindungan Hukum bagi Warga Rohingya yang Ditolak oleh Warga Aceh - Rachmawan, Farhan Dwi; Nurshah, Muhammad (Proceedings Series on Social Sciences & Humanities, 2024)
The Rohingya currently find that they are no longer getting a good response from the people around Aceh, especially in the West Aceh section, because some of them refuse some assistance from some of the surrounding communities and leave the refugee camp. This writing method uses a normative method with a juridical-normative approach which leads to legislation and applicable law. The results of this study will discuss the protection of rohingya citizens who fled their country because there were human rights issues where they fled from the government of another country and many victims of rohingya citizens were used as objects of human trafficking and then some of them fled to the West Aceh area and the stigma of the people of Aceh at that time changed from positive to negative due to the behavior of the rohingya citizens themselves and indeed Indonesia has not become a country that is a party to the 1951 refugee convention and the 1967 Protocol but Indonesia still respects the rights of asylum seekers such as the rohingya citizens themselves.